Proposed 4S Quality Metrics and Automated Continuous Quality (ACQ) Metrics Dashboard to Quantify Software Product Quality - Dheeraj; Sharma, Kalpana (International Journal of Computer Sciences and Engineering, 2019)
The purpose of this paper is to propose a set of test metrics required to quantify the quality of the software. A detailed research was done to analyse the testing process including functional, performance, security and usability testing around latest technologies covering cloud computing, big data, machine learning, artificial intelligence and internet of things. Effort, schedule, productivity, defects, quality and cost are fundamental parameters of any project. There are several metrics around these parameters covering all phases of project including project initiation, planning, executing, monitoring and controlling and closing. There was a time when weekly, monthly, quarterly or yearly metrics reports were published based on collected data. Confirming authenticity of that collected data was also a challenge. In current scenario looking at the adaption of continuous software engineering we proposed a new term called Automated Continuous Quality (ACQ) Metrics Dashboard which will act as product stability index or project health indicator. This could be used by organizations to track and generate all the required reports at real time. Any individual could select any of the project parameters for any period of time to generate a report. It would use continuous data collected by continuous monitoring of the tools.